A method for distinguishing the important malaria vectors anopheles dirus and an. Cracens (diptera: Culicidae) based on antennal sensilla of adult females - K. Taai (2020)
© 2019, Malaysian Society for Parasitology. All rights reserved. Some species of the Anopheles dirus species complex are considered to be highly competent malaria vectors in Southeast Asia. Anopheles dirus is the primary vector of Plasmodium falciparum and P. vivax while An. cracens is the main vector of P. knowlesi. However, these two species are difficult to distinguish and identify based on morphological characters. Hence, the aim of this study was to investigate the potential use of antennal sensilla to distinguish them. Large sensilla coeloconica borne on the antennae of adult females were counted under a compound light microscope and the different types of antennal sensilla were examined in a scanning electron microscope. The antennae of both species bear five types of sensilla: ampullacea, basiconica, chaetica, coeloconica and trichodea. Observations revealed that the mean numbers of large sensilla coeloconica on antennal flagellomeres 2, 3, 7, 10 and 12 on both antennae of both species were significantly different. This study is the first to describe the types of antennal sensilla and to discover the usefulness of the large coeloconic sensilla for distinguishing the two species. The discovery provides a simple, reliable and inexpensive method for distinguishing them.